A comparison of urban growth and their influencing factors of two border cities: Laredo in the US and Nuevo Laredo in Mexico. (February 2017) - Zhao, Chunhong; Jensen, Jennifer; Zhan, Benjamin
Abstract: The adjacent cities of Laredo in the US and Nuevo Laredo in Mexico have been growing at an unprecedented pace over the past decades. The trans-boundary flows of commodities and capital between these two cities, as well as significant population growth have created an interdependent system in this area. This characteristic provides an opportunity to thoroughly examine drivers behind landscape changes in the two cities. The aim of this study is to examine urban growth and the influencing factors of Laredo-Nuevo Laredo. Results of initial remote sensing-GIS analysis indicated that there was considerable urban expansion in both cities from 1985 to 2014. Spatially, Laredo demonstrated a more dispersed and rapid growth pattern compared to Nuevo Laredo. Additional results from a logistic regression using data at the pixel level on both sides of the border revealed a number of factors that influenced urban growth for both cites. These factors included: (1) elevation, (2) distance to nearest urban clusters, (3) distance to local roads, and (4) density of urban pixels. In addition, this study found that some dominant variables (population density and density of highways) affected urban growth differently for the two cities. Furthermore, globalization factors related to industrial activities/maquiladoras also played a significant role in affecting urban growth although the trajectories were not completely clear. Highlights: Total built-up areas in Laredo and Nuevo Laredo increased by 227.5% from 1985 to 2014. Laredo demonstrated a more disperse growth pattern compared to that in Nuevo Laredo. Elevation, distance to nearest urban clusters, distance to local roads, and density of urban pixels affected urban growth. Population density and density of highways had different effects in urban growth. Globalization related to industries/maquiladoras also played a significant role on urban growth.